Measurement of nasal index in Bhaktapur region: a descriptive cross-sectional study - Makaju, Sarbada; Adhikari, Shradha; Rai, Chandra Kala (Journal of Chitwan Medical College, 2022)
Background: The nose is most projection part of the face. Anatomically, the shape of the nose is pyramidal with its apex faces upward and the base faces downwards. It plays an important role in respiration, phonation and aesthetic. The shape of the nose varies according to the different geographical region owing to climate and ethnicity. The aim of this study was to assess the nasal index among the citizens of Bhaktapur. Methods: The study was conducted on 385 population of Bhaktapur between 1 Aug 2020-Aug 2021. The frequency of the nasal index was analysed. The vernier calliper was used to measure the height and width of nose. The data was analysed by using Statistical Package for the Social Sciences 20 version. Results: In this study, the highest prevalence of nasal index in Bhaktapur region was mesorrhine 235 (61.0%). In the gender, the highest prevalence of the Nasal Index was mesorrhine. In the ethnicity also mesorrhine types of the Nasal Index was found. Conclusions: This study concludes that commonest nasal index of the population of Bhaktapur fall under mesorrhine type of nose. The sexual dimorphism was not significant in both the gender as it showed mesorrhine types in both gender. Whereas among the ethnicity, the Brahmin and Newar sharing the almost the same result.